Ethical issues pertaining to 'Student RFID Tag' / Norhamiza Yarani - Yarani, Norhamiza (2006)
Student RFID tag is a new technology that use in tracking student or children while their away from house. Some school in US had done a pilot test to their students. However, parents are angry and protest the pilot test for the reason of their children's privacy. Ministry of Education in Malaysia has received a proposal to use this technology here. This research seeks to determine the function of student RFID tag, the ethical issues that may arise from the implementation of it and also the guidelines in order to implement the technology with no issues will arise later. Two schools are involved in this research with 484 students and 4 teachers. Questionnaires are distributed to the students to know the perception of students toward student RFID tag and the issues. The results are students do care about their privacy and health and also hope that the implementation of RFID tag will not violate their privacy. This result shows that privacy and health are the issues that may arise from the implementation of student RFID tag and some guidelines need to be constructed and follow.